2017
DOI: 10.1002/leap.1111
|View full text |Cite
|
Sign up to set email alerts
|

Peer review: The experience and views of early career researchers

Abstract: This paper presents selected findings from the first year of a 3‐year longitudinal study of early career researchers (ECRs), which sought to ascertain current and changing habits in scholarly communication. Specifically, the aims of the paper are to show: (1) how much experience and knowledge ECRs had of peer review – both as authors and as reviewers; (2) what they felt the benefits were and what suggestions they had for improvement; (3) what they thought of open peer review (OPR); and (4) who they felt should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0
12

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 21 publications
5
47
0
12
Order By: Relevance
“…As noted by Rodríguez‐Bravo et al . (), ‘peer review can be seen as a form of schooling, which all ECRs have to endure in order to obtain security and to progress in their career’ (p. 275).…”
Section: Resultsmentioning
confidence: 99%
“…As noted by Rodríguez‐Bravo et al . (), ‘peer review can be seen as a form of schooling, which all ECRs have to endure in order to obtain security and to progress in their career’ (p. 275).…”
Section: Resultsmentioning
confidence: 99%
“…We asked them what the main reason for their preference was, and as expected (and as informed by the interviews), anonymity was the main reason (Table ). As we learned from the interviews, ECRs do not like putting their head above the water and attracting unwelcome criticisms (Rodríguez‐Bravo et al ., ). Around 40 used the ‘other’ option to provide more reasons for their choice.…”
Section: Resultsmentioning
confidence: 97%
“…The study also showed that many have experience in peer review (in both being reviewed and reviewing the work of others) and consider it a very important process. Although they want some small improvements, they do not want wholesale changes to the current system (Rodríguez‐Bravo et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Unfortunately, there are still too many examples of manuscripts receiving cursory reviews (Rodriguez‐Bravo et al, ). Reviewers need to be held accountable for such bad practices, primarily by the handling editor.…”
Section: Content Integritymentioning
confidence: 99%